Knowledge-Based and Intelligent Information and Engineering Systems, Part III 15th International Conference, KES 2011, Kaiserslautern, Germany, September 12-14, 2011, Proceedings, Part III - König, Andreas; Dengel, Andreas; Hinkelmann, Knut; Kise, Koichi; Howlett, Robert J.; Jain, Lakhmi C. (Lecture Notes in Artificial Intelligence,, 2011)
The four-volume set LNAI 6881- LNAI 6884 constitutes the refereed proceedings of the 15th International Conference on Knowledge-Based Intelligent Information and Engineering Systems,  KES 2011, held in Kaiserslautern, Germany, in September 2011.